(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In recent years, the ongoing reforms in education around the world, the modernization of existing teaching methods and technologies, improving the efficiency of the pedagogical process, enhancing the quality of teaching staff to create an effective model of education. In this regard, the ongoing renewal, change and reforms in our country are aimed at this goal. In order to increase the effectiveness of education, it is necessary to reform the education system, improve the quality and establish cooperation with developed countries in this regard. This article discusses the requirements for improving the quality of education in the higher education system, reforms in the process of reforming the higher education system, the creation of a new generation of educational and regulatory documents, taking into account the student’s labor intensity, the development of academic and professional flexibility of graduates, the introduction of a credit-modular system when introducing intensive methods of knowledge acquisition.